PUTUSAN MAHKAMAH KONSTITUSI YANG TIDAK DILAKSANAKAN DALAM PENGUJIAN UNDANG-UNDANG DITINJAU DARI ASAS ERGA OMNES (Analisis Putusan Mahkamah Konstitusi Nomor 1/PUU-XI/2013) - Fadly Ikhsan Pradana (2021)
Abstract The Constitutional Court in Indonesia was established based on the Amendment to the 1945 Constitution. One of the tasks performed by the Constitutional Court based on Article 24C paragraph (1) is to examine the laws and regulations under the Constitution. With regard to judicial review, Article 51 paragraph (3) of Law No. 24 of 2003 states that the judicial review is divided into two, namely formal testing and material testing. After the Constitutional Court gives the decision, the legislature and the executive must be implemented and obeyed in general (erga omnes). After the explanation above, it can be concluded that there are factors why the Constitutional Court's Decision is very difficult to carry out, both at the community level, state officials, or state institutions. This is because the decision of the Constitutional Court does not have a kind of institution that functions to carry out the execution of a decision issued by the Constitutional Court. Furthermore, the decision of the Constitutional Court can provide a clear grace period for state institutions and state officials to immediately implement the decision and provide administrative sanctions if there are state officials or state institutions that have not implemented the decisions issued by the Constitutional Court because if there are parties who do not implement the decision then can be said to have done contempt of court. Keywords: Judicial Review, Constitutional Court, Erga Omnes